(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
This study analyzes the constitutional duty of environmental protection through artificial intelligence, proposing that the State be held accountable for technological inaction in the face of international climate commitments. (Received: October 2025 | Accepted: November 2025)